PENENTU NIAT PEMBELIAN KEMBALI TIKET PESAWAT SECARA ONLINE PADA SITUS TRAVELOKA.COM - Megantara, I Made Toni; Suryani, Alit (E-Jurnal Manajemen; Vol 5 No 9 (2016), 2016)
The purpose of this study was to determine the effect of Online Trust, Previous Online Purchase Experience, Brand Orientation, Quality Orientation, towards Repurchase Intention. The research was conducted on consumers Traveloka domiciled in Denpasar. Sempl e retrieval using non-probability methods side by purposive sampling with responsen amounted to 120 people. Data were collected using a questionnaire. Data analysis technique used is the technique of Multiple Linear Regression analysis. The results showed that (1) The Online Trust positive and significant effect on the Repurchase Intention., (2) Previous Online Purchase Experience positive and significant impact on the Repurchase Intention., (3) Brand Orientation positive and significant effect on the. Repurchase Intention, (4) Quality Orientation positive and significant effect on the Repurchase Intention
Keywords: Online Trust, Previous Online Purchase Experience, Brand Orientation, Quality Orientation, Repurchase Intention